Response of selected tropical grasses to irrigation with brackish water - U. R., Sangakkara (Universiti Putra Malaysia Press, 1994)
Agricultural development programmes in the sandy regions of the dry zone of Sri Lanka envisage the establishment of suitable fodder for livestock under irrigation programmes using brackish underground water. A study evaluated the response of three popular tropical grasses and the natural species to irrigation with brackish water having conductivities ranging from 0.5-6.0 ms. cm, when established in a sandy soil. The study was carried out for 6-7 months, with regular irrigation to correspond to the dry season. Growth of all three species was affected by increasing conductivity of water. Brachiaria mutica was affected to the greatest extent. Yields of Paspalum dilatatum were reduced to a lesser extent with increasing brackishness of water. Panicum maximum produced the highest yield and provided a significant quantity offodder in all treatments. However, the introduced species outyielded the natural species with the exception of Brachiaria at the higher levels of conductivity. The data illustrated the effect of brackishness on the yielding ability of the selected species. The practical significance of the study in terms ofpossible uses of these species in growing grasses under irrigation in the sandy tracts for herbage production in the dry season is presented.